The Influence of Optimism Bias on Time and Cost on Construction Projects - Aaron Chadee; Salisha R. Hernandez; Hector Martin (Emerging Science Journal, 2021)
The unresolved scholarly debate to curtail cost and time performances in projects has led to alternate solutions, departing from the dominant technical school of thought to include concepts from behavioural sciences. In this paper, we consider the psychological effect, namely optimism bias, as one of the root causes for delays in cost overruns on projects. The research objectives were to determine the level of bias among project participants, rank time and cost overrun causes according to the participants’ bias score and establish a mitigation strategy to curb potential delays and cost overrun impacts based on the bias scores obtained. A literature survey was conducted to determine causal factors contributing to delays and cost overruns linked to optimism bias. Through a pilot survey of three semi-structured interviews, eighty factors obtained from the literature survey were reduced to 24 critical delay and cost overrun factors relevant to Trinidad and Tobago. A questionnaire was subsequently developed seeking construction professionals to rate their bias scores based on an 11-point Likert scale. The research confirms that project planners and decision-makers exhibit moderate levels of optimism bias; however, participants lacked awareness of the impact of optimism bias on projects outcomes. Project location, environmental impacts and historic preservation, and labour disputes are the top three critical factors where project professionals displayed increased optimistic tendencies. It is proposed that contingency “time window” and reference class forecasting be implemented as control mechanisms to mitigate the impacts of time and cost overruns on projects. This research introduces a novel method to account for and measure optimism bias on construction projects. This study adds knowledge into delays and cost overruns causation and provides a foundation for future studies on quantifying psychological effects on projects and enhancing overall project management practices. Doi: 10.28991/esj-2021-01287 Full Text: PDF